THE USE OF COFFEE HUSK FIBER IN THE MAKING OF POLYMER CONCRETE WITH POLYESTER RESIN AS A BINDER - Awan Maghfirah; Heni Meilanda; Eddy Marlianto; Mulkan Iskandar Nasution (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2019)
Research of polymer concrete had been made by using sand, pumice, coffee shell fiber and polyester resin. Research had been done in order to get the best combination. Then, it has pressd by using Hot Press at temperature of 90°C for 30 minutes. The properties of polymer concrete has been analyzed that physical properties such as density, porosity, water absorbtion, mechanical properties, bending strength, compressive strength, tensile strength and photograph analysis by SEM-EDX. The result of research showed that the best combination based on test was sand 60 g, pumice, coffee shell fibe, and polyester resin with ratio of (8:2:30) gr that density 1,62 g/cm3; porosity 1.70%; water absorbtion 1.04%; bending strength 7.40 MPa; compressive strength 10.92 MPa; and tensile strength 4.13 MPa. Keywords: Coffee shell fiber, polymer concrete, pumice, and sand.